Berberis aristata combined with Silybum marianum on lipid profile in patients not tolerating statins at high doses. Issue 1 (March 2015) - Derosa, Giuseppe; Romano, Davide; D'Angelo, Angela; Maffioli, Pamela
Abstract Aim To evaluate the effects of Berberis aristata combined with Silybum marianum in dyslipidemic patients intolerant to statins at high doses. Methods 137 euglycemic, dyslipidemic subjects, with previous adverse events to statins at high doses, were enrolled. Statins were stopped for 1 month (run-in), then they were re-introduced at the half of the previously taken dose. At randomization, patients tolerating the half dose of statin, were assigned to add placebo or B. aristata/S. marianum 588/105 mg, 1 tablet during the lunch and 1 tablet during the dinner, for six months. We evaluated lipid profile and safety parameters variation at randomization, and after 3, and 6 months. Results B. aristata/S. marianum reduced fasting plasma glucose (−9 mg/dl), insulin (−0.7 μU/ml), and HOMA-index (−0.35) levels compared to baseline and also to placebo. Lipid profile did not significantly change after 6 months since the reduction of statin dosage and the introduction of B. aristata/S. marianum, while it worsened in the placebo group both compared to placebo and with active treatment (+23.4 mg/dl for total cholesterol, +19.6 mg/dl for LDL-cholesterol, +23.1 mg/dl for triglycerides with placebo compared to B. aristata/S. marianum). We did not record any variations of safety parameters in nether of groups. Conclusions B. aristata/S. marianum can be considered as addition to statins in patients not tolerating high dose of these drugs.